Mathematic Anxiety : Persepsi dan Remaja - Dewi Roso Wulandari; Karsoni Berta Dinata (Universitas Muria Kudus, 2026)
Understanding adolescents' perspectives on mathematics anxiety is anticipated to be the most effective method of overcoming obstacles to learning in mathematics classes. This study investigated adolescents' perceptions of mathematics anxiety. Descriptive qualitative research methods were employed with high school students in the tenth-grade students at MA Al Mubarok Baturaja, Lampung Utara as participants. The research instrument was interviews, and data were collected through semi-structured face-to-face interviews. Thematic data analysis was the method of data analysis adopted in this investigation. The results showed that mathematics anxiety in adolescents is a physical and mental phenomenon that triggers self-protection mechanisms such as drowsiness. Despite being stressed by abstract material and rigid assessments, they are still able to maintain general self-confidence. Educators need to create an emotionally safe classroom atmosphere through a gamification approach and supportive feedback. In addition, providing coping strategies and a growth mindset is crucial for building resilience so that emotional obstacles do not hinder students' cognitive potential